Methodological Aspects of Researching Trust in Management Sciences - Lewicka, Dagmara; Krot, Katarzyna; Książek, Dawid (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
This article presents an overview of the problems associated with the study of trust in management science. Trust can be considered in various contexts and ranges. Its varied sources and dimensions, cultural roots and numerous other features have made it difficult to analyse and reconcile in the research done by various authors. Another reason studying trust is difficult is that it is a cognitive construct, and it is often researched based on the subjective perception of respondents. The article attempts the most comprehensive approach to issues of trust with regard to the problems associated with measuring it.